Evaluating the Effects of Maternal Vitamin D Supplementation on the Subsequent Growth Performance and Carcass Characteristics of a Subsample Population of Growing Pigs - J. R. Flohr; J. C. Woodworth; M. D. Tokach; S. S. Dritz; R. D. Goodband; J. M. DeRouchey; J. R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2015)
A subsample of 448 growing pigs (PIC 327 × 1050), or approximately 50% of pigs weaned from sows fed varying dietary vitamin D regimens, were used in a split-plot design to determine the influence of maternal and nursery vitamin D regimens on growth performance. Sows were previously administered diets containing vitamin D as either: 1) low vitamin D3(363 IU/lb); 2) medium vitamin D3(907 IU/lb); 3) high vitamin D3(4,354 IU/lb); or 4) 23μg 25(OH)D3/lb (Hy-D, DSM Nutritional Products Inc, Parsippany, NJ) as described by Flohr et al. (20153) throughout gestation and lactation. A total of 52 total litters from 2 consecutive weaning groups were represented in the subsample population for growth performance. Once weaned, pigs were allotted to pens in the nursery based on previously administered maternal vitamin D regimens, then pens were randomly assigned to 1 of 2 nursery vitamin D regimens (907 IU of vitamin D3/lb, or 23μg 25(OH)D3/lb). Pigs remained on nursery vitamin D regimens for 35 d, then they were provided common growing and finishing diets until market. One pig per pen was bled at weaning and on d 17, 35, and 70 post-weaning to determine growing pig serum vitamin metabolites. At weaning, pig BW was increased (quadratic, P = 0.001) with increased maternal vitamin D3supplementation. This was because pigs from sows fed the medium concentration of vitamin D3were heavier at weaning compared to pigs from sows fed the low or high concentration of vitamin D3. Overall from d 0 to 35 in the nursery, pigs from sows fed increasing vitamin D3had increased (quadratic, P<0.003) ADG and ADFI, but F/G was similar regardless of maternal Vitamin D regimen. Pigs from sows fed the low concentration of vitamin D3had poorer (P<0.002) ADG and final nursery BW compared to those from sows fed 25(OH)D3. Throughout finishing (d 35 post-weaning until market), ADG was increased (quadratic, P = 0.005) and ADFI tended to increase (quadratic, P = 0.055) with increasing maternal vitamin D3supplementation because pigs from sows fed the medium concentration of vitamin D3had greater ADG and numerically greater ADFI compared to pigs from sows fed the low or high concentration of vitamin D3. Average daily gain of pigs from sows fed the low concentration of vitamin D3was lower (P<0.004) compared to those from sows fed 25(OH)D3. Carcass data were also collected from 734 pigs (approximately 65% of pigs weaned from sows administered vitamin D regimens) from 3 out of the 4 weaning groups used for the experiment. At marketing, live BW and HCW were heavier (P<0.030) for pigs from sows fed 25(OH)D3compared to pigs from sows fed the high concentration of vitamin D3. Also, percentage carcass yield increased (quadratic, P = 0.003) with increasing maternal vitamin D3supplementation. Loin depth (linear P = 0.047) and BF (quadratic, P = 0.031) were both decreased with increasing vitamin D3supplementation. Overall, it appears that vitamin D3 and 25(OH)D3, whether through maternal supplementation or through the diet, are useful sources of vitamin D to increase serum 25(OH)D3concentrations in growing pigs. Additionally, 25(OH)D3(in the nursery diet) can increase serum 25(OH)D3of nursery pigs more than feeding the same international unit equivalency of vitamin D3. Pigs from sows fed the medium concentration of vitamin D3performed better after weaning compared to pigs from sows fed the low or high concentrations of vitamin D3; however, this difference may have been confounded with the variance in weaning weight associated with the subsample population used for the growth portion of the study. Also, it is perceived that pigs from sows fed 25(OH)D3had increased live weight and HCW compared to pigs from sows fed the high concentration of vitamin D3.
Keywords: 25(OH)D3; growth; finishing pig; nursery pig; vitamin D